Infecções hospitalares em pacientes idosos: aspectos epidemiológicos clássicos e moleculares associados a Staphylococcus aureus e Enterococcus spp - Ribas, Rosineide Marques (2003)
Three one-week survey was conducted to determine the prevalence rate of nosocomial infections in elderly patients (65 years of age or older). We examined nosocomial and community infections rates and their relationship with intrinsic and extrinsic risk factors in a Brazilian University Hospital. Additionally, a colonization survey was carried out from their nares, oropharynx and intestine the presence of Staphylococcus aureus and Enterococcus spp. Finally, a laboratory surveillance was conducted during the period to detected nosocomial bacteremias by this organisms considering adults patients and elderly patients. Isolates were identified to species levei by classical methods and antimicrobial susceptibility by using gel diffusion and diluition methods. mecA gene and van genes were investigate in MRSA isolates (“Methicillin- resistant Staphylococcus aureus”) and Enterococcus spp., respectively, by polymerase chain reaction. The pulsed-fíeld gel electrophoresis (PFGE) pattems to eleven Enterococcus isolates recovered in different clinics/services was performed. The overall prevalence of elderly patients with nosocomial and community infections were 16,1% and 25,6%, respectively without dififerences when compared with adults patients. On the other hand, when the elderly group was considered almost all risk factors (use of antibiotics, invasive devices, surgery and time o f hospitalization) were found to be significantly associated with hospital infection. The colonization rate for Staphylococcus aureus was high (55,6% in nostril and 38,9% in intestine), with 39% o f the isolates oxacillin resistant. Risk factors to nosocomial bacteremias by MRSA included: more than one diagnostic, surgery, time o f hospitalization, use o f antibiotics and devices invasives, but was not related with advanced age (60 years of age or older). We describe the first isolate of vancomycin-resistant Enterococcus faecalis (vanA) in a surgical patient, poly-traumatic, vancomycin and 3thcephalosporins treated. The strain was clonally related as shown by PFGE to another isolate who was not the same ward and was treated of different time.